Developmental Commitment in Dictyostelium discoideum - Katoh, Mariko (American Society for Microbiology (ASM), 2007)
Upon starvation, Dictyostelium discoideum cells halt cell proliferation, aggregate into multicellular organisms, form migrating slugs, and undergo morphogenesis into fruiting bodies while differentiating into dormant spores and dead stalk cells. At almost any developmental stage cells can be forced to dedifferentiate when they are dispersed and diluted into nutrient broth. However, migrating slugs can traverse lawns of bacteria for days without dedifferentiating, ignoring abundant nutrients and continuing development. We now show that developing Dictyostelium cells revert to the growth phase only when bacteria are supplied during the first 4 to 6 h of development but that after this time, cells continue to develop regardless of the presence of food. We postulate that the cells’ inability to revert to the growth phase after 6 h represents a commitment to development. We show that the onset of commitment correlates with the cells’ loss of phagocytic function. By examining mutant strains, we also show that commitment requires extracellular cyclic AMP (cAMP) signaling. Moreover, cAMP pulses are sufficient to induce both commitment and the loss of phagocytosis in starving cells, whereas starvation alone is insufficient. Finally, we show that the inhibition of development by food prior to commitment is independent of contact between the cells and the bacteria and that small soluble molecules, probably amino acids, inhibit development during the first few hours and subsequently the cells become unable to react to the molecules and commit to development. We propose that commitment serves as a checkpoint that ensures the completion of cooperative aggregation of developing Dictyostelium cells once it has begun, dampening the response to nutritional cues that might inappropriately block development.